The Relation of the Motive Sport Achievement and Self-confidence with the Level of Achievement of Throwing Events in Athletics - Ahmed, Dr. Bilal Ali (International Journal of Psychosocial Rehabilitation, 2020)
The sports movement has witnessed a rapid and effective development in the past years, and this development has occurred as a real result of many studies and researches conducted in the individual and different games, including throwing events that have developed the levels of achievement of players physically, skillfully, and psychologically. there are various methods and means of training in order to compete for the greatest possible distance in these events, so the importance of research came to know the motivation towards achievement as an engine for archers ’behavior, and self-confidence as a general trend that represents the psychological goal of the thrower and the ability to achieve specific patterns of behavior and the relationship of these psychological variables to the achievement of throwing events for athletics and finding the best ways to explain their relational in a manner that ensures the development of achievements and performance for archers and the judiciary on the fluctuating levels of throwers in the athletics federation, being dependent on the results of psychological measurements that are important in the performance of the throwing events, including the motivation of the athletic achievement of the player, their measurement and the identification of the motivation of the players, as well as the sports self- confidence of the throwers. The research sample included (45) of the Iraqi Athletics Federation throwers who are under the age of (20) years, and when the training staff was able to identify the player’s initial motivation towards achievement and to identify the engine of his sports behavior in achieving a good result commensurate with his physical capabilities, provided by the staff The training includes opportunities for success and repetition of performance in which he gained self-confidence and performance in a manner that suits the capabilities of the player in general, where through these psychological features and their enhancement can reach the best achievement and eliminate cases of weakness and fluctuation levels.